A taxonomy of users' active design engagement in the 21st century. (March 2020) - Kohtala, Cindy; Hyysalo, Sampsa; Whalen, Jack
Abstract : People not only purchase and use products and services, but creatively appropriate, hack, redesign and even innovate in them. Typologies of active use have emerged in various disciplines, remaining piecemeal even if complementary. Together they produce a blurry depiction of active design engagement, despite active use being pivotal to many emerging design approaches. To remedy this, we synthesize a taxonomy of different aspects of active use and design engagement. Use as-is, active use, locally new designs and globally new innovations mark different intensities of engagement. These can concern the material form of design, new uses, new meanings, adjustment to local settings, or the collective endeavours to shape communities and organizations, ideologies and imaginaries, and global platforms that facilitate active use. Highlights: People do not only purchase and use products; they design, appropriate and innovate. Research on active users in different fields highlight different characteristics. We synthesize a taxonomy on active design engagement from existing literature. Active use is pivotal to many design approaches for decades, and increasingly so. We illustrate the taxonomy with examples from peer-to-peer open design making.